BIoT-DApp: A Prototype for Real Time Traceability in Agricultural Supply Chains - Sajid Safeer; Victoria Lemieux; Chang Lu; Cataldo Pulvento (Emerging Science Journal, 2026)
Agricultural supply chains frequently experience inefficiencies, including a lack of transparency, post-harvest losses, and inequitable compensation for stakeholders. This study aims to develop and evaluate a Blockchain-IoT decentralized application (BIoT-DApp) that enhances traceability, efficiency, and resilience in agri-food supply chains. Utilizing a lab-based prototyping methodology, the system integrates Ethereum smart contracts with IoT sensors to automate workflows from cultivation to retail, employing a hybrid architecture that stores raw sensor data off-chain while anchoring cryptographic hashes on-chain. The methods involve designing role-specific smart contracts, managing batch life cycles across six stages, and conducting real-time environmental monitoring through IoT data processed by Raspberry Pi, with deployment and testing performed on the Sepolia testnet. The findings demonstrate automated quality control, reduced storage costs through optimized on-chain practices, and seamless product ownership transfers validated by four role-based MetaMask accounts representing a farmer, wholesaler, retailer, and end-user. Core functions were executed successfully, with gas costs ranging from 30,000 (data logging) to 112,300 (batch initialization), confirming both cost efficiency and scalability. The novelty of this work lies in bridging blockchain theory and practice by providing a modular, adaptable prototype capable of supporting perishable agricultural supply chains globally. This offers policymakers and agri-tech developers actionable insights for decentralized solutions in resource-constrained environments.